2011
DOI: 10.1063/1.3578450
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-diffusion analysis for one-step plasma etching and bonding of microfluidic devices

Abstract: The role of electric charge in microdroplets impacting on conducting surfaces Physics of Fluids 22, 051703 (2010); https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…We found that, with increasing etching duration, there was increased cell attachment, notably more “penetration” of cell attachment incrementally by a few hundred microns toward the interior of the patterning template, also reflected in higher cell attachment ratios in 3b and 3c (ϕ = 0.886 ± 0.082 and 0.868 ± 0.112) compared to 3a (ϕ = 0.464 ± 0.031). This finding was consistent with previous reports that showed plasma etching is limited by the extent of plasma ion diffusion into microchannels . Penetration of plasma ions into microchannels depends on the oxygen plasma settings, including duration, partial pressure of oxygen, and power. , Cell attachment on hydrophilic microtracks with no protein coating showed lower density and cell spreading than Matrigel-coated surfaces.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that, with increasing etching duration, there was increased cell attachment, notably more “penetration” of cell attachment incrementally by a few hundred microns toward the interior of the patterning template, also reflected in higher cell attachment ratios in 3b and 3c (ϕ = 0.886 ± 0.082 and 0.868 ± 0.112) compared to 3a (ϕ = 0.464 ± 0.031). This finding was consistent with previous reports that showed plasma etching is limited by the extent of plasma ion diffusion into microchannels . Penetration of plasma ions into microchannels depends on the oxygen plasma settings, including duration, partial pressure of oxygen, and power. , Cell attachment on hydrophilic microtracks with no protein coating showed lower density and cell spreading than Matrigel-coated surfaces.…”
Section: Results and Discussionsupporting
confidence: 92%
“…This finding was consistent with previous reports that showed plasma etching is limited by the extent of plasma ion diffusion into microchannels. 45 Penetration of plasma ions into microchannels depends on the oxygen plasma settings, including duration, partial pressure of oxygen, and power. 46,47 Cell attachment on hydrophilic microtracks with no protein coating showed lower density and cell spreading than Matrigel-coated surfaces.…”
Section: Mechanism Of Fluorosilane-based Micropatterningmentioning
confidence: 99%
“…Previously, this concept has only been carried out to create surfaces that contain patterns of physisorbed proteins within microfluidic channels. 15,16 More labor intensive methods, without patterns, involve the manufacturing of glass-glass microfluidic † Electronic supplementary information (ESI) available. See DOI: 10.1039/ c9an02407g a Laboratory of BioNanoTechnology, Wageningen University and Research, Bornse Weilanden 9, 6708 WG Wageningen, the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this concept has only been carried out to create surfaces that contain patterns of physisorbed proteins within microfluidic channels. 15,16 We are advocating Open Technologies such as ESCARGOT, 17 for cheap microfluidics and HARICOT, 18 for responsive materials: here we present the COMPLOT concept: Covalent monolayer patterns in Microfluidics by Plasma etching Open Technology. Therefore, introducing covalent surface modification, as presented here, provides the user with a reliable and cost-friendly patterning Fig.…”
Section: Introductionmentioning
confidence: 99%